The Effect of Nutrition Education Using Leaflet Media on Knowledge of Meal Planning in Type II Diabetes Mellitus Outpatients at the Pasundan Health Center in Samarinda - Devina Nur Astiza; Joko Cahyono; Diah Retno Wahyuningrum (Formosa Journal of Science and Technology, 2023)
Diabetes mellitus is a degenerative disease that cannot be fully cured, but can be managed and controlled by the sufferer. The knowledge of a person with diabetes mellitus is greatly influenced by the information obtained, informative and interesting educational media is a very strong supporting factor in increasing knowledge quickly. The purpose of this study was to determine the effect of nutrition education using leaflet media on knowledge in type II diabetes mellitus outpatients at the Pasundan Health Center in Samarinda. The pre-experimental research design used the One Group Pretest-Postest design with 40 respondents using a purposive sampling technique. Data analysis used the Wilcoxon test with a value of p=0.000. The results showed that there was a difference in the average value of knowledge before and after being given nutrition education using leaflet media. So that there is an influence of nutrition education using leaflet media on the knowledge of type II diabetes mellitus outpatients.